Implementation of a Standardized Protocol for Postpartum Anemia: A Prospective Cohort Study - Lower, Casey A.; Gleason, Emily G.; Toda, Asaki; Srinivas, Sindhu K.; Levine, Lisa D.; Power, Maggie E.; Hamm, Rebecca F. (American Journal of Perinatology, 2024)
Implementation of standardized protocols for antepartum anemia increases intravenous iron (IVFe) use and improves predelivery hemoglobin (Hb). However, this condition is often overlooked and inadequately treated in postpartum care settings. We aimed to determine if implementation of a standardized protocol for postpartum anemia increases postpartum IVFe use and affects clinical outcomes.We performed a prospective cohort study evaluating implementation of a standardized inpatient protocol for postpartum anemia. This protocol, implemented in December 2021, recommends (1) IVFe for postpartum Hb 7.0 to 8.9 g/dL and (2) oral iron for postpartum Hb 9.0 to 9.9 g/dL. We compared all postpartum inpatients at a single site from April 2021 (preimplementation period [PRE]) to April 2022 (postimplementation period [POST]). The primary outcome was any IVFe use. Secondary outcomes included number of IVFe doses, oral iron supplementation at discharge, postpartum complications, and length of stay.A total of 805 patients were included (PRE = 401; POST = 404). Patients in the PRE and POST groups differed in ethnicity (PRE: 8.2% Hispanic vs. POST: 14.9% Hispanic, p = 0.003). IVFe use significantly increased from PRE to POST (PRE: 6.0% vs. POST: 11.1%, p = 0.009) even when controlling for differences between groups (adjusted odds ratio: 2.48, 95% confidence interval: [1.08–5.67]). Patients receiving IVFe in the POST group were more likely to receive the recommended three doses of IVFe compared with patients receiving IVFe in the PRE group (POST: 29% vs. PRE: 4%, p = 0.04). Patients in the POST group had shorter lengths of stay than in the PRE group (POST: 1.69 days vs. PRE: 1.81 days, p < 0.001). There were no significant differences in blood transfusion, oral iron supplementation, or postpartum complications.Implementation of a standardized protocol for postpartum anemia increased IVFe use without increasing length of stay.
Keywords: postpartum anemia; intravenous iron; protocol; implementation; postpartum hemorrhage